2017
DOI: 10.1121/1.5012746
|View full text |Cite
|
Sign up to set email alerts
|

Temporal characteristics of contextual effects in sound localization

Abstract: Two experiments examined plasticity induced by context in a simple target localization task. The context was represented by interleaved localization trials with the target preceded by a distractor. In a previous study, the context induced large response shifts when the target and distractor stimuli were identical 2-ms-noise clicks [Kopčo, Best, and Shinn-Cunningham (2007). J. Acoust. Soc. Am. 121, 420-432]. Here, the temporal characteristics of the contextual effect were examined for the same stimuli. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 31 publications
2
20
2
Order By: Relevance
“…The analysis of the spatial properties of CP showed that 1) CP is observed as a repulsion of responses away from the adaptor location that decreases with separation between target and adaptor, and that 2) the effect is stronger in the variable context condition where the overall adaptor click rate is higher. These results are consistent with previous studies (Hládek et al, 2017; Kopčo et al, 2015) but extends the finding to lateral as well as frontal adaptors. Additionally, we find that variable and fixed context effects are similar both in their strength and spatial extent for the frontal and lateral adaptor when expressed as a function of distance from the adaptor, suggesting that the spatial representation in which CP is induced is approximately uniform, even though auditory spatial resolution decreases with azimuth (Hartmann & Rakerd, 1989).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The analysis of the spatial properties of CP showed that 1) CP is observed as a repulsion of responses away from the adaptor location that decreases with separation between target and adaptor, and that 2) the effect is stronger in the variable context condition where the overall adaptor click rate is higher. These results are consistent with previous studies (Hládek et al, 2017; Kopčo et al, 2015) but extends the finding to lateral as well as frontal adaptors. Additionally, we find that variable and fixed context effects are similar both in their strength and spatial extent for the frontal and lateral adaptor when expressed as a function of distance from the adaptor, suggesting that the spatial representation in which CP is induced is approximately uniform, even though auditory spatial resolution decreases with azimuth (Hartmann & Rakerd, 1989).…”
Section: Discussionsupporting
confidence: 94%
“…The additional adaptation in the variable context showed either a constant or an approximately linear growth, uniform over the whole duration of the current runs. This again shows that the variable context, randomly switching between a 1-click and an 8-click adaptor, causes the adaptation to have a very slow component, much slower than those observed in our previous studies (e.g., (Hládek et al, 2017)) and resulting in a stronger CP. Note that the additional adaptation would likely have reached an asymptotic value if the runs were sufficiently long.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…To estimate the distance of a source, listeners have access to a broad variety of acoustic cues like sound intensity, reverberation characteristics (often quantified by the direct-to-reverberant energy ratio), near-field ILDs, the shape of the stimulus spectrum, and others (for review, see Kolarik et al, 2016). The relative perceptual relevance of these cues and their underlying neural codes are the subject of debate and are most probably dependent on the context (for a review, see Hládek et al, 2017). Recent studies suggest that the amount of temporal ILD fluctuations and amplitude modulation depth likely represent reverberation-related cues (Catic et al, 2015).…”
Section: Sound Localizationmentioning
confidence: 99%